Ventricular fibrillation associated with complete right bundle branch block - Aizawa, Yoshiyasu; Takatsuki, Seiji; Kimura, Takehiro; Nishiyama, Nobuhiro; Fukumoto, Kotaro; Tanimoto, Yoko; Tanimoto, Kojiro; Miyoshi, Shunichiro; Suzuki, Makoto; Yokoyama, Yasuhiro; Chinushi, Masaomi; Watanabe, Ichiro; et al. (Heart rhythm, 2013)
A substantial number of patients with idiopathic ventricular fibrillation (IVF) present with no specific electrocardiographic (ECG) findings. To evaluate complete right bundle branch block (RBBB) in patients with IVF. Patients with IVF showing complete RBBB were included in the present study. Structural and primary electrical diseases were excluded, and provocation tests were performed to exclude the presence of spastic angina or Brugada syndrome (BrS). The prevalence of complete RBBB and the clinical and ECG parameters were compared either in patients with IVF who did not show RBBB or in the general population and age and sex comparable controls with RBBB. Of 96 patients with IVF, 9 patients were excluded for the presence of BrS. Of 87 patients studied, 10 (11.5%) patients showed complete RBBB. None had structural heart diseases, BrS, or coronary spasms. The mean age was 44 ± 15 years, and 8 of 10 patients were men. Among the ECG parameters, only the QRS duration was different from that of the other patients with IVF who did not show complete RBBB. Ventricular fibrillation recurred in 3:2 in the form of storms, which were well suppressed by isoproterenol. Complete RBBB was found less often in control subjects (1.37%; P < .0001), and the QRS duration was more prolonged in patients with IVF: 139 ± 10ms vs 150 ± 14ms (P = .0061). Complete RBBB exists more often in patients with IVF than in controls. A prolonged QRS complex suggests a conduction abnormality. Our findings warrant further investigation of the role of RBBB in the development of arrhythmias in patients with IVF.